Manufacture, structure and electrophysical properties of YSZ/SrTixZr1-xO3 solid solution; Ceramics International; Vol. 46, iss. 18, Pt. A - Sudzhanskaya I. V. Irina Vasiljevna (2020, 2020)
Title screen